System of indicators for the evaluation of the quality of the virtual component in the accreditation of university careers - Feliciano Alexis Torres-Francisco; Yanyorky Sánchez-Pérez; Kobel Guerrero-Muguercia (Universidad de Guantánamo, 2018)
The progressive implementation of the virtualization in Higher Education has generated important changes in the complex dynamics of educational processes. These changes generate problematic edges and critical points that must be identified and analyzed with the aim of designing strategies that make possible to improve the quality of this virtual educational offer. In this sense, important aspects related to historical evolution and theoretical-methodological conceptions on the evaluation of the quality of university careers are taken as reference points, basic conceptual the authors propose a system of indicators and its methodology of practical instrumentation for the evaluation of the quality of the virtual component of university careers within the framework of the accreditation process, conceived as a guidance for the evaluation process conceptually and methodologically, and to improve, therefore, the quality of the training services, and thus reach, optimal levels of professionalization. The feasibility of the proposal was evaluated based on the application of the Expert Criteria method, which corroborated that it is feasible and applicable in correspondence with the purposes that guided its elaboration.